Penerapan Program Kolintang Masuk Gereja: Meningkatkan Pemahaman Musik dan Mengembangkan Aspek Mental-Spiritual-Kolaboratif di Gereja Pantekosta di Indonesia - Soegiarto Hartono; Djoko Santoso; Antonius Suparno (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2025)
This community service program aims to implement kolintang in church settings to enhance congregational understanding of music while fostering mental, spiritual, social, and collaborative aspects. The method used is community education and training through Kolintang Pedagogy, which integrates body movements, visuals, rhythm, and harmonic patterns to facilitate musical comprehension. This approach also utilizes Directional Chord Symbols, an intuitive harmonic notation system that enables participants to grasp the relationships between notes and chords more effectively in kolintang performance. The program was conducted among women’s and children’s groups in three Pentecostal churches in Indonesia (Banten and East Java). The results showed significant improvements: (1) musical harmony comprehension increased from 25% to 85%, (2) kolintang playing skills improved from 5% to 70%, (3) kolintang was successfully integrated into church worship, and (4) community bonding was strengthened through collective musical activities. This program not only preserves Indonesia’s cultural heritage but also enriches the congregation’s spiritual experience through an inclusive and innovative musical approach.